Electrochemical Strategy for Detection of Biomolecules - Felisilda, Bren Mark Balane (Curtin University, 2018)
The search for affordable, fast and sensitive biomolecular detection techniques continue as challenges for early disease diagnostics, therapeutics, and environmental remediation. The use of the electrochemistry at the interface between two immiscible electrolyte solutions (ITIES) promises to be a viable tool for label-free detection. This study investigates the use of this method in the characterization and detection of proteins, sulfated poly- and disaccharides, and aptamers. The data presented here not only advances the understanding of biomolecular behaviour at the ITIES but also offers novel insights into ways of enhancing detection within biomimetic matrices.